Manurial value of khat waste vermicompost from Awday, Harar town, Ethiopia - Hiranmai Yadav Rameshwar; Anteneh Argaw (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Catha edulis, commonly called as khat or chat is an evergreen plant cultivated in Ethiopia for its stimulant leaves. The young leaves are chewed as a part of social recreation and the older leaves along with the twigs are discarded. This forms the major part of municipal solid waste that is dumped in large quantity in Harar region. The present study was carried in Haramaya University, Ethiopia to decompose the khat wastes along with crop residues and different animal manures (cow dung, goat manure, poultry manure and swine manure) using the earthworm Eisenia foetida. Methods The collected khat wastes along with crop residues and different animal manures were vermicomposted and assessed for nutrient contents using standard procedures. Results The result of the experiment indicated that all the parameters were improved by the decomposition using earthworms and the C/N ratio was within the limits that indicate the maturity of the compost. The organic carbon, organic matter, total nitrogen, phosphorus, copper, iron, zinc and manganese contents were analyzed and found to be improved after decomposition. The added crop residues and animal manures enhanced the decomposition process and manurial value of the khat leaf waste. Conclusion The nutrient content of the vermicomposts revealed khat to be a suitable substrate for vermicomposting thereby making efficient utilization of solid wastes. This can be an effective technology to reduce the solid waste and the resultant product can be used for improving soil fertility and crop production by the farmers.